Biologic efficacy optimization--a step towards personalized medicine. - Kiely, Patrick D. W. (Rheumatology, 2016)
This following is a review of the factors that influence the outcome of biologic agents in the treatment of adult RA and, when synthesized into the clinical decision-making process, enhance optimization. Adiposity can exacerbate inflammatory diseases; patients with high BMI have worse outcomes from RA, including TNF inhibitors (TNFis), whereas the efficacy of abatacept and tocilizumab is unaffected. Smoking adversely affects TNFi outcomes but has less or no effect on the efficacy of rituximab and tocilizumab, and the effect on abatacept is unknown. Patients who are positive for ACPA and RF have better efficacy with rituximab and abatacept than those who are seronegative, whereas the influence of serotype is less significant for tocilizumab and more complex for TNFis. All biologics seem to do better when co-prescribed with MTX, whereas in monotherapy, tocilizumab is superior to adalimumab and prescription of a non-MTX DMARD has advantages over no DMARD for rituximab and adalimumab. Monitoring of TNFi drug levels is an exciting new field, correlating closely with efficacy in RA and PsA, and is influenced by BMI, adherence, co-prescribed DMARDs and anti-drug antibodies. The measurement of trough levels provides a potential tool for patients who are not doing well to determine early whether to switch within the TNFi class (if levels are low) or to a biologic with an alternative mode of action (if levels are normal or high). Conversely, the finding of supratherapeutic levels has the potential to enable individual patient selection for dose reduction without the risk of flare.